2017
DOI: 10.1186/s12936-017-1828-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anti-malarial interventions on trends of malaria cases, hospital admissions and deaths, 2005–2015, Ghana

Abstract: BackgroundSince 2005, the Government of Ghana and its partners, in concerted efforts to control malaria, scaled up the use of artemisinin-based combination therapy (ACT) and insecticide-treated nets (ITNs). Beginning in 2011, a mass campaign of long-lasting insecticidal nets (LLINs) was implemented, targeting all the population. The impact of these interventions on malaria cases, admissions and deaths was assessed using data from district hospitals.MethodsRecords of malaria cases and deaths and availability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…While multiple studies demonstrated the effect of LLIN programmes on P. falciparum incidence (e.g. [25,26]), evidence from settings with several Plasmodium species is scarce. Although it has been suggested that the impact of vector control on P. vivax may be delayed due to the parasite's biology, this study only found short-term transient increases in the proportion of P. vivax by light microscopy, suggesting that at intermediate to high transmission, both species are affected by vector control and both species may resurge.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple studies demonstrated the effect of LLIN programmes on P. falciparum incidence (e.g. [25,26]), evidence from settings with several Plasmodium species is scarce. Although it has been suggested that the impact of vector control on P. vivax may be delayed due to the parasite's biology, this study only found short-term transient increases in the proportion of P. vivax by light microscopy, suggesting that at intermediate to high transmission, both species are affected by vector control and both species may resurge.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual improvement in the data capture and reporting, through the DHIMS infrastructure, at the district level in government health facilities and faith based private facilities across the country were accounted for by allowing for various levels of reporting and system improvements from 2008 to 2018. Years of improvement in all suspected cases receiving a malaria diagnostic test was also incorporated (Fig 3) [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The roll out of LLINs on a large scale basis in Ghana begun from 2003 [59]. This resulted in a substantial improvement in the proportion of households with at least one LLIN as well as at least one LLIN per every two members of a household (universal coverage) across the country [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in transmission potential for young children, adults and pregnant women were also considered. The gradual improvement in the data capture and reporting, through the DHIMS infrastructure, at the district level in government health facilities, faith based private facilities across the country were accounted for by allowing for various levels of reporting and system improvements from 2008 to 2018 while years of improvement of malaria diagnosis was also incorporated [21,22].…”
Section: Discussionmentioning
confidence: 99%